Ranking of Zahedan’s Five Districts in Order to Fulfill the Creative City - Rezazadeh, Masoumeh Hafez; Sancholi, Badil; Rad, Saeideh Salimi; Feyzabadi, Abolfazl Nazmi; Kadkhodaei, Mehdi (Journal of History Culture and Art Research, 2017)
Moving towards the development and realization of the creative city due to the status of the city as a place of forming knowledge society contexts, and the importance of cities in economic development is very necessary and important. This paper aims to examine the components of the creative city in Zahedan and tries to move toward urban creativity. Considering the components of this research, it is an applied study, which is conducted through a descriptive-analytical method. The research includes 20 indicators for the creative city. A researcher made questionnaire is used to collect data. In addition, SPSS and GIS softwares are used to analyze the data. The statistical population is the five districts of Zahedan City, in which 383 residents were selected and studied through cluster and systematic random sampling in all districts of the city. The ranking results of districts in the creative city indicators show that district 1 is the most desirable district and district 3 is the most undesirable and the most deprived district with informal and disturbed settlements. The effectiveness of each component of the creative city indicators was studied in the regression analysis. It was found that the effectiveness of all components is not identical in the realization of the creative city in Zahedan. They act in the form of a chain and the stability of the chain depends on the planning and investment in all of the sub-indicators of these components.